History, Political Elite and the Struggle for Nigerian Unity, 1960 —2010 - Undiyaundeye, Udida (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
While some British colonial authorities never hid their disdain for the concept of a Nigerian nation, others along with their bosses in the Colonial Office felt it would take Nigerians over a century to attain nationhood. At every opportunity that offered itself, the former used it to emphasize how widely disparate Nigerian peoples were on the one hand; and Nigerian peoples and their educated compatriots on the other. The 1945 constitution was one of those cogs that were thrown in the path of Struggle for nationhood. Regrettably, the Nigerian political elite did not see things, any much differently as they did cooperate with the colonial authorities and continued to pay lip services to the concept of a Nigerian nation even in the Post Colonial setting, evidenced by their policies that if anything, engendered and emphasized those things that separate rather than unite Nigerians. History, a tool for national cohesion and development, is so recognized by Nigerian peoples. Its trained practitioners in Nigeria have shown that the colonial authorities only quickened the pace of the unification of Nigeria; as all the ingredients for the evolution of Nigeria were already in place when the colonial authorities came. They have also pointed to the negative effect of the activities and utterances of the political elite on national unity but to avail. This paper seeks to deepen our understanding of the dynamics that informed the negative actions of both the colonial authorities and the political elite which in their aggregate have retarded Nigerian national unity.